2004
DOI: 10.4038/jccpsl.v9i1.8275
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the dietary pattern of adolescent schoolgirls in two defined urban and rural settings

Abstract: Objectives: To compare the dietary pattern and somerelated factors among adolescent schoolgirls in two defined urban and rural settings. Methodology: A-_crosi-sectional comparative study was carried out among adolescent schoolgirls in year eleven classes, attending selected Grade 1AB schools in two defined urban and rural settings. A selfadministered questionnaire which included a food frequency questionnaire was used to assess the food habits and some relevant factors such as independence of dietary habits, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…[ 7 , 21 ] However, a majority of students (73.3%) consumed a home-prepared breakfast, the finding of which is also consistent with the study reported by Kumarapeli. [ 22 ] Individual practices related to diet may be dependent on family food choices as well as availability, accessibility, and affordability which are influenced by the fluctuations in cost due to weather conditions experienced throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 21 ] However, a majority of students (73.3%) consumed a home-prepared breakfast, the finding of which is also consistent with the study reported by Kumarapeli. [ 22 ] Individual practices related to diet may be dependent on family food choices as well as availability, accessibility, and affordability which are influenced by the fluctuations in cost due to weather conditions experienced throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of Sri Lankan women have poor knowledge on proper nutrition during pregnancy and lactation 23 and there are no published reports in Sri Lanka regarding the prevalence of pre-conceptional FA intake. Little is known about what motivates young women to become informed about the use of FA supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of estate adolescents (34%) who restricted food purposely to avoid obesity and who restricted food during menstruation (36.8%) were similar to the finding of the study among adolescents in urban and rural Sri Lanka (37.4% and 36.1% respectively). 21 All the other factors, low dietary diversity, food purchase at each meal/ daily, and poor food availability, which were found to be associated with estate adolescent undernutrition as revealed by the multivariate analysis were related to inadequate access/availability of food and can be considered to be caused largely by poverty at household level. Some experiences of food unavailability can be considered to indicate situations in which adolescent females of the poor households had to compromise their share of food to give priority to others.…”
Section: Experience Frequency Percentagementioning
confidence: 86%
“…The proportion of estate adolescents (34%) who restricted food purposely to avoid obesity and who restricted food during menstruation (36.8%) were similar to the finding of the study among adolescents in urban and rural Sri Lanka (37.4% and 36.1% respectively). 21…”
Section: Discussionmentioning
confidence: 99%